Pengaruh Masrahiyyah Terhadap Kemampuan Critical Thinking dan Berbicara Bahasa Arab Mahasiswa UIN Malang - Nabilah, Farah Farhatun; Abidin, Munirul (Maharaat Lughawiyyat: Jurnal Pendidikan Bahasa Arab, 2025)
This study aims to examine the influence of masrahiyyah activities on the critical thinking and Arabic speaking (kalam) skills of students in the Arabic Language Education Department (PBA) at UIN Malang. As a drama-based instructional method, masrahiyyah engages students in scriptwriting and role-playing, thereby enhancing both linguistic and cognitive skills. This research employed a quantitative approach using a correlational survey method. Data were collected from 42 respondents consisting of students and alumni of the PBA program at UIN Malang who participated in masrahiyyah, through an online questionnaire. The data were analyzed using SPSS, including tests of validity, reliability, and multiple linear regression analysis. The findings indicate that masrahiyyah has a significant positive impact on both speaking (kalam) ability and critical thinking. However, the influence on speaking skills is greater than that on critical thinking. This study highlights masrahiyyah as an effective strategy for promoting communicative and analytical competence in Arabic language learning.